Pharmacological interventions for preventing post-operative atrial fibrillation in patients undergoing cardiac surgery: a network meta-analysis protocol - Wang, Xiaoqin (BMJ Open, 2017)
INTRODUCTION: Postoperative atrial fibrillation (POAF) is the most common complication following cardiac surgery, and randomised clinical trials (RCTs) and systematic reviews have been conducted to compare and evaluate different pharmacological interventions for preventing POAF. This study aimed to explore the effect of different pharmacological interventions for prophylaxis against POAF after cardiac surgery using network meta-analysis (NMA). METHODS AND ANALYSIS: A systematic search will be performed in PubMed, EMBASE and the Cochrane Library to identify RCTs, systematic reviews, meta-analyses or NMA of different pharmacological interventions for POAF. We will evaluate the risk of bias of the included RCTs according to the Cochrane Handbook V.5.1.0, and use GRADE to assess the quality of evidence. Standard pairwise meta-analysis, trial sequential analysis and Bayesian network meta-analysis will be used to compare the efficacy of different pharmacological interventions. ETHICS AND DISSEMINATION: Ethics approval and patient consent are not required as this study is a meta-analysis based on published studies. The results of this NMA and trial sequential analysis will be submitted to a peer-reviewed journal for publication. PROTOCOL REGISTRATION NUMBER: CRD42017067492.